THE IMPLEMENTATION OF SKETCH TO STRETCH STRATEGY IN IMPROVING THE STUDENTS’ READING COMPREHENSION - Wida Sari; Sudarmanto; Maming, Khadijah (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2022)
The students’ reading comprehension need to be improved. One of the problems is caused by the teachers that still depend on the text book to teach students in teaching reading comprehension. Therefore, the researchers proposed a solution to overcome this problem by implementing a different learning strategy, namely sketch to stretch strategy. This research objective was to find out whether the implementation of sketch to stretch strategy able to improve the students’ reading comprehension. The researchers used a pre-experimental design with one group pretest and posttest design. The population of this research was the second-grade students of SMP Negeri 2 Suppa. The sample of this research was class VIII.2 consists of 23 students. In collecting data, the researchers used a reading comprehension test which was divided into pretest and posttest. The technique of analysis data used mean score and t-test formula for an independent sample. The findings demonstrated that the result of mean score in post-test (78.04) was higher than the mean score in pre-test (49.1). The posttest standard deviation was (10.1). At a significance level of 0.05 and a degree of freedom (df) of 22, the value of the t-test (17.558) was higher than the t-table (1.717). As a result, hypotheses H0 was rejected and H1 was accepted. The researchers concluded that implementation of sketch to stretch strategy improves the reading comprehension competence of the students.